Recurrent Diffuse Large B-Cell Lymphoma with the Initial Manifestation of Retinal Involvement - Wan-Ting Yeh; Jen-Tsun Lin* (Journal of Cancer Research and Practice)
Diffuse large B-cell lymphoma (DLBL) is a common hematological disorder that frequently presents with fever and lymphadenopathy initially. Here, we present an unusual case of a 43-year-old female with a history of breast DLBL in remission. She visited the ophthalmologist 9 years after remission with the chief complaint of ocular congestion, watery discharge, and blurred vision for weeks. The optical coherent tomography revealed hyper-reflective material accumulation in the intraretinal and subretinal pigment epithelial spaces. Then, she received a retinal biopsy to confirm the etiology, and the pathology report revealed necrosis with atypical lymphocytes with CD20 positivity. Thus, the intravascular lymphoma was impressed. The whole-body positron emission tomography/computed tomography revealed no hypermetabolic extracranial malignancy. Hence, the patient received six cycles of systemic chemotherapy along with intrathecal chemotherapy and refused either radiation therapy or bone marrow transplantation. The patient achieved complete remission with no recurrence for 3 years until the present.